(untitled) (Singaporean Journal of Business Economics and Management, 2024)
The impact of financial assistance on the performance of SMEs in six Nigerian states chosen from each geopolitical zone was investigated in this study using a mixed-methods approach that combined surveys and semi-structured interviews. Stratified and simple random sampling techniques were used to select respondents for the questionnaire, and 260 valid responses were returned for analysis. Although governments have made significant efforts to stimulate growth and development in the SME sector through various support initiatives, the increasing failure and underperformance of SMEs suggests that these efforts may not be as effective as expected. Additionally, 20 managers and owners of SMEs participated in semi-structured interviews. The quantitative data was analyzed using multiple regression and descriptive statistics, and the qualitative data was analyzed using thematic analysis. The results showed that although financial aid has a big influence on SME performance, it is frequently insufficient and hampered by irrational demands and red tape. The study suggests that increasing access to adequate capital is a crucial component of boosting SME performance in light of the study findings.